2019
DOI: 10.1111/cogs.12725
|View full text |Cite
|
Sign up to set email alerts
|

Teleological Essentialism

Abstract: Placeholder essentialism is the view that there is a causal essence that holds category members together, though we may not know what the essence is. Sometimes the placeholder can be filled in by scientific essences, such as when we acquire scientific knowledge that the atomic weight of gold is 79. We challenge the view that placeholders are elaborated by scientific essences. In our view, if placeholders are elaborated, they are elaborated by Aristotelian essences, a telos. Utilizing the same kind of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 26 publications
7
69
2
Order By: Relevance
“…This might be related to the normative and teleological nature of essentialism. If people indeed see essences in the context of purposes (Rose & Nichols, 2019) and these purposes are normatively good (De Freitas, Tobia, Newman & Knobe, 2017, p. 397), then it makes perfect sense that a human being should be viewed as essentially moral and well disposed towards others, and thus capable of forming good quality interpersonal relationships. Well-functioning society is, after all, naturally desirable for any social species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related to the normative and teleological nature of essentialism. If people indeed see essences in the context of purposes (Rose & Nichols, 2019) and these purposes are normatively good (De Freitas, Tobia, Newman & Knobe, 2017, p. 397), then it makes perfect sense that a human being should be viewed as essentially moral and well disposed towards others, and thus capable of forming good quality interpersonal relationships. Well-functioning society is, after all, naturally desirable for any social species.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to the question why social traits are more important than other kinds of traits might lie in the normative and teleological nature of essentialism. People seem to think about the essences of various entities in terms of their purpose, a telos (Rose & Nichols, 2019), and, at the same time, the traits that are believed to support personal identity are predominantly normatively good (De Freitas, Tobia, Newman & Knobe, 2017, p. 398). This logic that connects normativity and teleology could also be applied to human beings: if the purpose of the music band is to make good-quality music and the purpose of scientific papers is to carry valuable scientific information, then the purpose of a person is to be morally good (De Freitas, Tobia, Newman & Knobe, 2017, p. 397).…”
Section: Current Knowledgementioning
confidence: 99%
“…But there may be other pathways to essentialism as well. For instance, Rose and Nichols (2019) recently found that essentialist beliefs can reflect the ultimate purpose, or telos, of a category. This work on teleological beliefs investigated non-social natural kinds (e.g., spiders), but it is possible that telos is another pathway to essentialist beliefs about social groups in addition to biology and shared values.…”
Section: Essentialism As a General Heuristicmentioning
confidence: 99%
“…This way actions and tools are interpreted as means toward ends, which are goals of actions. Such functional, or teleological, representations are present in the written record since antiquity (Aristotle), ubiquitous across cognitive domains in humans (Kelemen & Rosset 2009;Rose & Nichols 2019;Talanquer 2007) and evident from early on in human infancy (Gergely & Csibra 2003;Hernik & Csibra 2015;Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%